(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2019)
In keeping with our promise, BFA SHOW-2019, a graduation exhibition, remained a moment of great joy and pride. On August 29, 2019, the show was inaugurated by Shri Sarbendra Khanal, Inspector General of Nepal Police amidst a gala ceremony. As usual, the show showcased an impressive of works created by our out-going graduate students. it represented all the courses of studies, we offer in our college and the works remained a composite collection, accumulated over one academic years. In addition to being a grand reflection of the creative strength of our students, present show also, sought to portray a new up and coming dimension of their education they received in our college.